Management of lower respiratory tract infections (LRTI’s): clinical microbiologists’ perspective - Ramana, K V (International Journal of Research in Medical Sciences, 2017)
In the era of emergence and re-emergence of newer and existing microorganisms, clinical and laboratory diagnosis of LRTI’s requires regular evaluation. Elaborating on possible predisposing factors will be critical to health care workers in the better management of patients suffering with Lower Respiratory Tract Infections (LRTI’s). Microbiologist’s role becomes crucial in deciding the culture methods to be employed to isolate the suspected causative microorganism and identification of the probable pathogen among mixed growth of the isolated bacteria/fungi. Antimicrobial therapy should necessarily be guided by the susceptibility patterns of various antibiotics against different microorganisms from a given geographical region, which should be regularly updated.